Effectiveness of autologous cell products derived from adipose tissue for the treatment of severe local radiation injuries - Eremin P.S.; Pigaleva N.A.; Murzabekov M.B.; Lebedev V.G.; Lazareva N.L.; Eremin I.I.; Pulin A.A.; Osipov A.N.; Bushmanov A.Yu.; Kotenko K.V. (Саратовский научно-медицинский журнал, 2014)
Aim: to investigate the dynamics of ulcer surface healing depending on type of radiation ulcer and cell product in murine experimental model of severe local radiation injuries after exposure to X-rays. Material and Methods. Mature Wistar rats were used for experiments (males, weight 180-200 grams). Standard model of severe local radiation injuries was used: X-ray irradiation of animals on a modified RAP100-10 device. Isolation of the stromal-vascular fraction carried out by enzymatic treatment of adipose tissue. Autologous cells transplantation performed on day 20 after irradiation in the case of acute radiation injury model (early radiation ulcers) and day 120 in the case of long-term effects of radiation injury model (chronic radiation ulcers). As a positive control allogeneic MMSC derived from rat bone marrow were used. Results. Application of autologous cell products derived from adipose tissue in animal model of severe local radiation injuries was investigated for the first time. It was shown that usage of stromal vascular fraction of adipose tissue for the treatment of early radiation injuries not only leads to better improvement (as compared with the use of MMSCs), but also pronounced therapeutic effect could be observed at an earlier time. On the model of long-term effects of radiation injuries therapeutic effect was observed for all cell products. Conclusion. Cell-based products derived from adipose tissue are promising material for future research and clinical application for treatment of local radiation injuriesK) Described method allows choosing treatment strategy basing on patient's individual characteristics and the type of local radiation injuries.